Cloud System for Software Testing (International Journal of Engineering and Computer Science, 2017)
Software testing is a process of implementation programs and applications to find errors in software. Testing of a large number of software at the same time may take a long time and cost a lot. This paper describes a distributed system for software testing depends on cloud computing principles. Virtualization is used to provide possibilities in network creation and it's parts. Capturing the network traffic shows that when the file size is increased, the time taken to test is increased too. When one tester is used and two users, the test process took longer time, so it's needed to increase testers.